2015
DOI: 10.1007/s00706-015-1628-z
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of unusual Ga2O3 polymorphs

Abstract: A comparative structural and spectroscopic study, combined with reactivity tests in (inverse) water-gas shift and methanol steam reforming reaction, has been performed on various Ga 2 O 3 polymorphs with special focus on δ-Ga 2 O 3 and ε-Ga 2 O 3 with the aim of highlighting the eventual intrinsic physico-chemical properties of the latter two. Using this comparative approach, the question whether δ-Ga 2 O 3 in fact is a nanocrystalline modification of ε-Ga 2 O 3 , a mixture of ε-Ga 2 O 3 and β-Ga 2 O 3 or a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…There are several polymorphs of Ga 2 O 3 , which were investigated in detail both experimentally and theoretically by: Roy et al [8], Zinkevich and Aldinger [9], Penner et al [10], Playford et al [11], Yoshioka et al [12], Delgado and Areán [13], Fornari et al [14], and Cora et al [15]. Although as many as six polymorphs (α, β, γ, δ, ε, and κ) having different crystallographic systems and formation temperatures have been reported for Ga 2 O 3 (table 1), there are likely four polymorphs: α, β, γ, and (δ/ε/κ).…”
Section: Polymorphism Of Ga 2 Omentioning
confidence: 99%
“…There are several polymorphs of Ga 2 O 3 , which were investigated in detail both experimentally and theoretically by: Roy et al [8], Zinkevich and Aldinger [9], Penner et al [10], Playford et al [11], Yoshioka et al [12], Delgado and Areán [13], Fornari et al [14], and Cora et al [15]. Although as many as six polymorphs (α, β, γ, δ, ε, and κ) having different crystallographic systems and formation temperatures have been reported for Ga 2 O 3 (table 1), there are likely four polymorphs: α, β, γ, and (δ/ε/κ).…”
Section: Polymorphism Of Ga 2 Omentioning
confidence: 99%
“…Solid-state 71 Ga NMR spectra were recorded using either a Bruker Avance II or Bruker Avance NEO console equipped with a 20.0 T wide-bore superconducting magnet (Larmor frequency of 259.3 MHz) and Bruker 1.3 mm double-broadband HXY probe (MAS rates of 50−55 kHz) or JEOL 1 mm double-resonance probe (MAS rate of 75 kHz) at the UK 850 MHz solid-state NMR facility. 71 Ga MAS NMR spectra were recorded using a rotor-synchronized spin-echo pulse sequence with an echo delay of one rotor period (i.e., 13 a recycle interval of 0.5−2 s. Chemical shifts are reported in parts per million relative to aqueous Ga(NO 3 ) 3 using either LaGaO 3 (δ iso = 57 ppm) or GaPO 4 berlinite (δ iso = 111.2 ppm) as secondary solid references.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Gallium oxide polymorphism had received comparatively little attention until 5 years ago, when an interest in the electronic properties of various forms of the materials has attracted a growing amount of attention, in particular in microelectronics where the large band gap of β-Ga 2 O 3 offers new possibilities in high-frequency power devices, but also in photocatalysis where mixtures of polymorphs can lead to cooperative behavior at phase junctions. , Much of the previous understanding of the structures of gallium oxide polymorphs stemmed from the work of Roy and co-workers in the 1950s, , and until recently, the polymorphism in the Ga–O, Ga–(OH), and Ga–O–(OH) systems remained poorly characterized despite a large number of publications on the structural characterization of gallium oxide. The recent work of some of us clarified the structures of a number of gallium oxide polymorphs, some of which contain inherent structural disorder leading to poor crystallinity. , The thermodynamically stable polymorph under ambient conditions is the monoclinic β-polymorph (in contrast to the α-polymorph for aluminum oxide) whose structure contains a 1:1 octahedral:tetrahedral cation ratio, both in distorted coordination geometry . α-Ga 2 O 3 , structurally analogous to α-Al 2 O 3 , is metastable, but β-Ga 2 O 3 irreversibly converts to this polymorph at high pressure because α-Ga 2 O 3 has a smaller molar volume .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the position of these peaks is in good agreement with cubic δ-Ga 2 O 3 phase (ICDD card (6-529)), which was characterized as isomorphic to Tl 2 O 3 or bixbyite (Mn,Fe) 2 O 3 structures [12,13]. In more recent works it was shown that the δ-Ga 2 O 3 does not exist as an independent phase and is a nanocrystalline form of the ε-Ga 2 O 3 with an amorphous layer of nitrate and hydroxide groups around gallium oxide particles [2,11,14]. The formation of ε-Ga 2 O 3 with increasing tin content will be discussed below for the samples obtained by annealing at 750 • C. The tincontaining phases are not clearly observed.…”
Section: Annealing Temperature 500 °Cmentioning
confidence: 99%